Bully, bullied and abused. Associations between violence at home and bullying in childhood. Issue 1 (February 2016) - Lucas, Steven; Jernbro, Carolina; Tindberg, Ylva; Janson, Staffan
Aims: The aim was to examine experiences of bullying among Swedish adolescents and whether victims and perpetrators were also exposed to violence in the home, with particular focus on how abuse severity affected the risk of exposure to bullying. Methods : A nationally representative sample of pupils aged 14–15 responded to a questionnaire exploring exposure to corporal punishment and other types of violence. Results were analysed using Pearson's chi-square and multiple logistic regression, adjusting for factors regarding the child, the parents and the families' socioeconomic status. Results : Among the 3197 respondents, a significant proportion reported at least one incident of either bullying victimisation (girls 36%, boys 26%) or bullying perpetration (girls 24%, boys 36%). Physical and emotional violence in the home, including witnessed intimate partner violence, were significantly associated with both bullying victimisation and bullying perpetration. Odds ratios for exposure to bullying rose with increasing frequency and severity of abuse. Adjusted odds ratios ranged from 1.6 for any event of abuse vs. single episodes of bullying to 20.3 for multiple types of abuse vs. many episodes of bullying. The child's gender and the presence of a chronic health condition were consistently associated with nearly all levels of abuse and bullying. Conclusions : Bullying experiences are common among youth and are clearly associated with abuse. Frequent bullying, whether as victim or perpetrator, warrants particular vigilance, as it appears to be an indicator of severe violence in the home.